Polyacrylonitrile‐Coordinated Perovskite Solar Cell with Open‐Circuit Voltage Exceeding 1.23 V. (30th December 2021) - Chen, Chen; Wang, Xiao; Li, Zhipeng; Du, Xiaofan; Shao, Zhipeng; Sun, Xiuhong; Liu, Dachang; Gao, Caiyun; Hao, Lianzheng; Zhao, Qiangqiang; Zhang, Bingqian; Cui, Guanglei; et al.
Abstract: In solution‐processed organic–inorganic halide perovskite films, halide‐anion related defects including halide vacancies and interstitial defects can easily form at the surfaces and grain boundaries. The uncoordinated lead cations produce defect levels within the band gap, and the excess iodides disturb the interfacial carrier transport. Thus these defects lead to severe nonradiative recombination, hysteresis, and large energy loss in the device. Herein, polyacrylonitrile (PAN) was introduced to passivate the uncoordinated lead cations in the perovskite films. The coordinating ability of cyano group was found to be stronger than that of the normally used carbonyl groups, and the strong coordination could reduce the I/Pb ratio at the film surface. With the PAN perovskite film, the device efficiency improved from 21.58 % to 23.71 % and the open‐circuit voltage from 1.12 V to 1.23 V, the ion migration activation energy increased, and operational stability improved. Abstract : Polyacrylonitrile which has C≡N groups was introduced to passivate the uncoordinated lead cations in perovskite films. The coordination of C≡N with the lead cation was much stronger than that of the normally used C=O group. It could also reduce the I/Pb ratio at the film surface. The device efficiency was improved from 21.58 % to 23.71 %, with the open‐circuit voltage enhanced from 1.12 V to 1.23 V.